An Anthology of Philosophy in Persia, Vol. 1 (Bloomsbury Academic, 2024)
The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Islamic Publications Ltd. The tradition of philosophy in the Persian-speaking world is extraordinarily rich, creative and diverse. This anthology, which is divided into three volumes, aims to communicate something of that richness and diversity.The term 'philosophy' is understood to in its widest sense to include theological debate, philosophical Sufism and philosophical hermeneutics (ta'wil). Extending over a period of more than two millennia, and showcasing translations by well-established scholars, the anthology offers complete bibliographical references throughout. For anyone interested in exploring, in all their varied manifestations, the fascinating